Dementia Rating Scale Pada Lansia di RW 1 Kelurahan Cungking Kabupaten Banyuwangi - Nabilah, Jihan; Mandagi, Ayik Mirayanti (Tadulako University, 2020)
The problems that occur in the elderly in RW 01 Cungking Village, Banyuwangi Regency are living alone, inability to remember posyandu time and inability to come without assistance so that the number of elderly posyandu arrivals has decreased. The research objective is to identify the level of dementia according to gender in the elderly RW 01 . This research is a quantitative study with cross sectional design. Data collection using the Dementia Rating Scale questionnaire instrument designed by Steven Mattis. The population and research sample consisted of 20 elderly people who were taken based on non random sampling techniques with purposive sampling. The results of the study were 15 people (71.4%) 15 did not have dementia, and 3 people (14.3%) had mild dementia and 3 people (14.3%) had moderate dementia. Women are more predominantly experiencing dementia than men. Mild dementia in women as many as 3 people (100.0%) and no man has mild dementia. Medium dementia were 2 people (66.7%) and 1 person (33.3%) men. The conclusion of measuring dementia is that most respondents did not experience dementia but still found respondents with mild and moderate dementia status. Most of the research respondents were female with a higher incidence of dementia than men. Suggestion of research results is to make efforts to monitor the health of the elderly, especially dementia because if there is an increase in elderly sufferers it will affect productivity.